Função motora grossa, habilidades funcionais e fenótipo comportamental de crianças com paralisia cerebral - Costa, Milena Luchetta da (2008)
Cerebral Palsy is defined as a group of disorders of movement and posture, non progressive but often changeable, caused by a lesion of the immature brain. The objectives of this study were: to quantify the gross motor function of children with cerebral palsy; to classify the children according to gross motor function level; to assess the functional abilities and the level of child care assistance needed; to draw the children behavioral profile; to identify the children general reasoning capacity and possible correlation between the studied variables. The sample was constituted of 30 children aged between 6 and 11 years and 11 months, who receive treatment at Associação de Reabilitação Infantil Limeirense and at "Casas André Luiz", in Guarulhos-SP, and their respective parents or responsible. The following data collection instruments were applied: a semi-structured questionnaire about the gestational conditions, labor and birth; Gross Motor Function Classification System, to classify the sample according to the clinical features severity; Gross Motor Function Measure, for assessment of the gross motor function and the Pediatric Evaluation of Disability Inventory Brazilian Version (PEDI) for evaluation of functional abilities. A child behavioral assessment was performed with the Child Behavior Checklist Brazilian Version (CBCL/6-18) and applied the Test of Nonverbal Intelligence (TONI-3) with the aim of measuring the nonverbal cognitive abilities. The results had shown a significant correlation between motor function and functional abilities in the areas of self care and mobility. The most frequent comorbidities found were prematurity and epilepsy, although only epilepsy seems to influence the functional performance. In the behavioral assessment, disturbs were found in these areas: activities and social participation, social problems and aggressive behavior. It was also found internalizing, externalizing and anxiety problems. It was possible to conclude that physical independence and the presence of epilepsy were important predictors for the involvement in daily life activities of the children and that diagnosis and treatment of behavioral problems must be early treated avoiding any complications and interference in other developmental areas. It is very important the psychological participation on these patients follow up with their parents/family, as well as preventive measures like acting on environment changing conditions in order to improve the behaviors which are considered problematic, aiming also to the improvement of quality of life for the family and the child.